2005
DOI: 10.1002/pi.1808
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal properties of bismaleimide blends based on hydroxyphenyl maleimide

Abstract: N-(4-hydroxyphenyl)maleimide was melt-blended with the glycidyl ether of bisphenol-A and various mole percentages of 4, 4 -(diaminodiphenylsulfone) bismaleimide. The cure behaviour of the resins was evaluated by differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA). The blends showed distinct reductions in the onset of cure (T o ) and peak exothermic (T exo ) temperatures. The blends cured at low temperatures exhibited glass transition temperatures (T g s) higher than the cure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Synthesized monomer, homopolymers and copolymers [HBMBS], [CBMBS-A] and [CBMBS-B] are characterized and structures are confirmed from FT-IR, 1 H NMR spectral analysis.Synthesized polymer compounds were screened out for anti-fungal activity. All polymer compounds showed good anti-fungal activity against the fungalstrains compared to the standard drug Griseofulvin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesized monomer, homopolymers and copolymers [HBMBS], [CBMBS-A] and [CBMBS-B] are characterized and structures are confirmed from FT-IR, 1 H NMR spectral analysis.Synthesized polymer compounds were screened out for anti-fungal activity. All polymer compounds showed good anti-fungal activity against the fungalstrains compared to the standard drug Griseofulvin.…”
Section: Resultsmentioning
confidence: 99%
“…), 1304 cm -1 (C-N-C), 1336 cm -1 asym and 1162 cm -1 sym. (S=O stre., Sulfonamide), 909 cm -1 (C-H bending), 837 cm -1 (C-H bending, Aromatic for 1,4 disubstitutions); 1 Step 1: …”
Section: Synthesis and Characterization Of Nn'-bis(maleimide)benzenementioning
confidence: 99%
“…In order to enhance the toughness of BMI resins without sacrificing the excellent thermal properties, some long-chain structure BMI resins are synthesized. 1,4,19 These BMI resins showed well performance on the mechanical properties, especially the fracture toughness of the cured resins, without significant reducing the heat resistance of the modified resins. 15 In this article, a mixed BMI resin system consisting of BDM, bis[4-(4-maleimidephen-oxy)phenyl)]propane (BMPP), and DABPA were studied.…”
Section: Introductionmentioning
confidence: 97%
“…Inorganic nanoparticles and whiskers are also used as flexibilizers to enhance fracture toughness of BMI resins. In order to enhance the toughness of BMI resins without sacrificing the excellent thermal properties, some long‐chain structure BMI resins are synthesized . These BMI resins showed well performance on the mechanical properties, especially the fracture toughness of the cured resins, without significant reducing the heat resistance of the modified resins …”
Section: Introductionmentioning
confidence: 99%
“…For these reason, modifications of epoxy resins or curing agents in both the backbone and pendant groups have been continuously investigated to improve the thermal and physical properties of cured epoxy resins. Many studies have been reported that improved the heat resistance of epoxy resins by increasing the crosslink density of the cured epoxy resin3 or by introducing bulky structures, such as dicyclopentadiene,4 biphenyl,5, 6 naphthalene,7, 8 fluorine, or maleimide 9–11…”
Section: Introductionmentioning
confidence: 99%